Comparison of the Effectiveness of Emotion Efficacy Therapy and Compassion-Focused Therapy on Dispositional Mindfulness and Illness Acceptance in Women with Multiple Sclerosis - Jafari Fesharaki, Elahe; Raeisi, Zohreh; Soltanizadeh, Mohammad; Etemadifar, Masoud; Sadat Sajjadian, Parinaz (Psychology of Woman Journal, 2025)
Objective: The present study aimed to compare the effectiveness of Emotion Efficacy Therapy (EET) and Compassion-Focused Therapy (CFT) on dispositional mindfulness and illness acceptance in women with MS. Materials and Methods: This study employed a quasi-experimental design with pretest-posttest and a control group. The statistical population included all women diagnosed with multiple sclerosis who referred to MS specialty centers in Isfahan during the second half of 2023. A total of 54 women with MS were selected through convenience sampling and were randomly assigned to three groups: Emotion Efficacy Therapy (18 participants), Compassion-Focused Therapy (18 participants), and control group (18 participants). The instruments used in this study included the Five Facet Mindfulness Questionnaire (Baer et al., 2006) and the Illness Acceptance Questionnaire (Bishop et al., 2015). Findings: The findings revealed that both therapeutic approaches were effective in improving dispositional mindfulness (except for the facets of acting with awareness and non-reactivity) and illness acceptance in women with multiple sclerosis. There was no significant difference in the effectiveness of the two therapies on the measured variables. Conclusion: The results suggest that both therapeutic approaches can be considered effective methods for enhancing mindfulness and illness acceptance in women with multiple sclerosis. Given their similar efficacy, the choice between these therapies can be based on client preference or therapist expertise.